2020
DOI: 10.13057/biodiv/d210821
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution pattern, bionomic, and demographic parameters of a new invasive species of armyworm Spodoptera frugiperda (Lepidoptera; Noctuidae) in maize of South Sumatra, Indonesia

Abstract: Abstract. Hutasoit RT, Kalqutny SH, Widiarta IN. 2020. Spatial distribution pattern, bionomic, and demographic parameters of a new invasive species of armyworm Spodoptera frugiperda (Lepidoptera; Noctuidae) in maize of South Sumatra, Indonesia. Biodiversitas 21: 3576-3582. The fall armyworm, Spodoptera frugiperda, has reportedly been found in Indonesia since 2019. The main hosts of this new invading insect are food crops and several other crops. This study aimed to examine the spatial distribution pattern, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
2
13
0
19
Order By: Relevance
“…because the highest mortality occurs when the population is getting older and few deaths at the beginning (Figure 8). Similarly, Hutasoit et al (2020) research states that the chance of survival of S. frugiperda decreases when it becomes the 6 th instar and pupa.…”
Section: Biology Of Fall Armywormmentioning
confidence: 99%
“…because the highest mortality occurs when the population is getting older and few deaths at the beginning (Figure 8). Similarly, Hutasoit et al (2020) research states that the chance of survival of S. frugiperda decreases when it becomes the 6 th instar and pupa.…”
Section: Biology Of Fall Armywormmentioning
confidence: 99%
“…Maize in Indonesia is currently facing a big problem in invasion and outbreaks of newcomer insect pests, namely the fall armyworm (Spodoptera frugiperda) (Lepidoptera: Noctuidae). S. frugiperda comes from South America (Nagoshi et al 2017;Otim et al 2018) and entered Indonesia for the first time on March 26, 2019 in West Sumatra, then in June 2019 it was found in Banten and West Java (Sartiami et al 2020) and now it has spread rapidly to various provinces in Indonesia, such as South Sumatra (Herlinda et al 2020b;Hutasoit et al 2020), Lampung (Lestari et al 2020), and Bengkulu (Ginting et al 2020). The fall armyworm has caused maize yield losses in Africa of 250-630 million US dollars per year (Bateman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These observations agree with those of Maruthadurai and Ramesh (2020) on fodder maize. Hutasoit et al (2020) and observed the fecundity as 1064-1662 eggs/ female on maize. The incubation period varied significantly with cereal hosts, minimum (2.00 days) was on maize and pearl millet.…”
Section: Resultsmentioning
confidence: 96%